Primary mediastinal myxoid liposarcoma - Ab. Hamid, Suzana; Abu Hassan, Hasyma; Mohamad Saini, Suraini; Abdul Rashid, Saiful Nizam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
In this study, we report an extremely rare case of liposarcoma which arises primarily in mediastinum. The patient appeared to have progressive dyspnoea and prolonged cough for a duration of one year. Chest radiograph and Computed Tomography (CT) of the thorax revealed a large right mediastinal mass with fatty component. It was confi rmed to be primary liposarcoma on histopathological examination.